LEGAL CERTAINTY AND JUSTICE FOR NON-FISCAL CREDITORS IN TAX CONFISCATION AND BANKRUPTCY PUBLIC CONFISCATION CONFLICTS - Natalia, Rachel; Suhariyanto, Didik; Iryani, Dewi (Awang Long Law Review, 2025)
Bankruptcy as a mechanism for collective debt settlement aims to realize a fair and proportionate distribution of debtors' assets based on the principle of pari passu prorata parte. However, the existence of the state's right of precedence in tax collection, as stipulated in Law Number 19 of 2000 concerning Tax Collection by Compulsory Letter, often causes conflicts with the principle of bankruptcy in Law Number 37 of 2004 concerning Bankruptcy and PKPU. This normative conflict creates legal uncertainty, especially for non-fiscal creditors whose rights have the potential to be marginalized. The Supreme Court Decision Number 557 K/Pdt.Sus-Pailit/2018 is important to examine because it illustrates the tension between the position of tax confiscation and general confiscation in bankruptcy, as well as the extent to which the principle of distributive justice and the principle of creditor equality can be applied. This research is a normative legal research with legislative, conceptual, and case approaches. The research data in the form of primary, secondary, and tertiary legal materials were collected through literature studies, then analyzed descriptively-analytically using the theory of legal certainty and the theory of distributive justice. The focus of the study is directed at legal certainty for non-fiscal creditors in tax seizure and public confiscation conflicts, as well as the application of the principle of distributive justice and the principle of pari passu prorata parte in bankruptcy practice in Indonesia. The results of the study show that Supreme Court Decision Number 557 K/Pdt.Sus-Pailit/2018 provides significant legal protection for non-fiscal creditors by rejecting the absolutism of the state's right of precedence, while reaffirming the principle of distributive justice in the distribution of bankruptcy assets. However, the legal certainty that was born was still formal because the inconsistency between the Bankruptcy Law and the Tax Law had not been fully harmonized. Therefore, regulatory reconstruction is needed to unify norms related to tax confiscation and general confiscation, as well as the consistency of Supreme Court jurisprudence in order to create fair and balanced legal certainty for all creditors.